2015
DOI: 10.1007/s12199-015-0466-2
|View full text |Cite
|
Sign up to set email alerts
|

Food intake survey of kindergarten children in Korea: Part 2 increased dietary intake of tin possibly associated with canned foods

Abstract: Objectives Dietary intake of tin (Sn) may be increased in some children in kindergartens in Korea. The present study was intended to examine this possibility and clarify the extent of the elevation. Methods 24-hour food duplicate and spot urine samples were collected in 2003-2004 from 108 4-6-year-old children (boys and girls combined) in 4 kindergartens (1 in Seoul and 3 in Jeju Island), as reported in a previous publication. These samples were employed in the present analyses to examine tin levels in the die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The food duplicate, urine and a small portion (ca. 5 g) of boiled rice samples were wet-ashed by heating in the presence of mineral acids as previously described in Part 2 of this series of articles [21]. The wet-ashed liquid samples were subjected to ICP-MS (inductively coupled plasmamass spectrometry) analyses for Cd and Pb determination.…”
Section: Instrumental Analysismentioning
confidence: 99%
“…The food duplicate, urine and a small portion (ca. 5 g) of boiled rice samples were wet-ashed by heating in the presence of mineral acids as previously described in Part 2 of this series of articles [21]. The wet-ashed liquid samples were subjected to ICP-MS (inductively coupled plasmamass spectrometry) analyses for Cd and Pb determination.…”
Section: Instrumental Analysismentioning
confidence: 99%
“…So, there is concern about the possible consumer exposure to trace metals through canned fruits that are frequently produced and stored in tinplate cans, and epidemiological results raise questions about the evidence underlying dietary recommendations to promote tinned fruit consumption as a part of a healthy diet (Aasheim et al, 2015). In particular, a recent study reported elevated Sn levels in urine collected from children in Korea (reaching up to 3 mg Sn/day for some children) and this was suspected to be related to the consumption of tin-canned foods and beverages, especially canned fruits (Yang et al, 2015). Similarly, the second French diet study conducted a few years ago revealed that canned fruits contained the highest levels of Sn (up to 8.55 mg/kg) (Millour et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Buculei, Gutt, Sonia, Adriana, and Constantinescu (2012), Buculei et al (2014) showed the importance of the organic protective coating and its properties (e.g., porosity) on the migration phenomenon. Yet, uncoated (or plain) cans are commonly used for fruits since color changes in fruit (e.g., apricot) pieces have been reported in lacquered cans (Tošković, Rajkivić, & Stanojević, 2005). Since canned fruits are acidic media (pH < 4.5) (Diviš, Šťávová, Pořízka, & Drábiková, 2017), they are expected to offer favored conditions for trace metals' release due to corrosion (Abdel-Rahman, 2015; Ansari et al, 2019;Reilly, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Dietary intake levels of inorganic tin from canned foods can vary widely because tin levels in canned food are, for example, affected by the use of lacquered vs. unlacquered cans, the acidity of the food, storage conditions, and the presence of agents that influence the extent of tin dissolution from the tin coating (Greig and Pennington; IPCS). Interestingly, several studies reported that the consumption of canned food is not associated with urinary tin levels (Hayashi et al, 1991; Shimbo et al, 2007; Shimbo et al, 2013; Yang et al, 2015). Diet is also a major route of exposure to organotin compounds.…”
Section: Introductionmentioning
confidence: 99%